(untitled) (Journal of Computational Mathematics, 2018)
The interior low-frequency electromagnetic dipole excitation of a dielectric sphere is utilized as a simplified but realistic model in various biomedical applications. Motivated by these considerations, in this paper, we investigate analytically a near-field inverse scattering problem for the electromagnetic interior dipole excitation of a dielectric sphere. First, we obtain, under the low-frequency assumption, a closed-form approximation of the series of the secondary electric field at the dipole's location. Then, we utilize this derived approximation in the development of a simple inverse medium scattering algorithm determining the sphere's dielectric permittivity. Finally, we present numerical results for a human head model, which demonstrate the accurate determination of the complex permittivity by the developed algorithm.